Target capture sequencing for the first Nigerian genotype I ASFV genome - Adeola, A.C.; Luka, P.D.; Xiang-Xiang Jiang; Zheng-Fei Cai; Oluwole, O.O.; Xian Shi; Oladele, B.M.; Olorungbounmi, T.O.; Boladuro, B.; Omotosho, O.; Okoro, V.M.O.; Dawuda, P.M.; et al. (Microbiology Society, 2023)
African swine fever (ASF) is a contagious viral disease that affects domestic pigs and wild boars, causing significant economic losses globally. After the first Nigerian outbreak in 1997, there have been frequent reports of ASF in pig-producing regions in the country. To facilitate control, it is important to understand the genotype and phylogenetic relationship of ASF viruses (ASFVs). Recent genetic analysis of Nigerian ASFV isolates has revealed the presence of both genotypes I and II; this is based on analysis of a few selected genes. Phylogenetic analysis of ASFV whole genomes highlights virus origins and evolution in greater depth. However, there is currently no information on the ASFV genome from Nigerian isolates. Two ASFV-positive samples were detected during a random survey of 150 Nigerian indigenous pig samples collected in 2016. We assembled near-complete genomes of the two ASFV-positive samples using in-solution hybrid capture sequencing. The genome-wide phylogenetic tree assigned these two genomes into p72 genotype I, particularly close to the virulent Benin 97/1 strain. The two ASFVs share 99.94 and 99.92 % genomic sequence identity to Benin97/1. This provides insight into the origin and relationship of ASFV strains from Nigeria and Italy. The study reports for the first time the determination of near-complete genomes of ASFV using in-solution hybrid capture sequencing, which represents an important advance in understanding the global evolutionary landscape of ASFVs.